67.6k views
5 votes
1/3 ( 3x + 9 ) = 5 - 3 ( x - 2 )

User JKor
by
4.7k points

2 Answers

4 votes

Answer:

x= 2

Explanation:

Multiply both sides of the equation by 3, since that it the reciprocal of 1/3.

3x+9= 15- 9(x-2)

Distribute -9 through the parenthesis.

3x+9= 15-9x+18

Add the numbers.

3x+9= 33- 9x

Move the variable to one side.

3x+9= 33- 9x

-3x -3x

9=33-12x

Subtract to both sides.

9= 33-12x

-33 -33

-24= -12x

Divide -12 to both sides.

-24= -12x

-12 -12

x=2

User Abhay Saraf
by
5.2k points
3 votes
use photomath if you don’t a understand! it will help you alot
1/3 ( 3x + 9 ) = 5 - 3 ( x - 2 )-example-1
User Francadaval
by
5.8k points